2019
DOI: 10.21511/imfi.16(1).2019.26
|View full text |Cite
|
Sign up to set email alerts
|

Force majeure events and stock market reactions in Ukraine

Abstract: This paper examines reactions in the Ukrainian stock market to force majeure events, which are divided into four groups: economic force majeure, social force majeure, terrorist acts, natural and technological disasters. More specifically, using daily data for the main Ukrainian stock market index (namely PFTS) over the period from January 1, to December 31, 2018 this study investigates whether or not force majeure events create (temporary) inefficiencies and there exist profitable trading strategies based on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The extant literature provides several empirical pieces of evidence on stock market responses to the major systemic events. The studies investigate the impact of major events, for instance, the Severe Acute Respiratory Syndrome (SARS) pandemic disease outbreak (Chen et al, 2007(Chen et al, , 2018Loh, 2006), natural disasters (Caporale et al, 2019;Tavor & Teitler-Regev, 2019;Wang & Kutan, 2013), corporate events (Maitra & Dey, 2012;Ranju & Mallikarjunappa, 2019;Seal & Matharu, 2018), public news (Li, 2018;Ormos & Vázsonyi, 2011) and political events (Beaulieu et al, 2006;Bash & Alsaifi, 2019;Ismail & Suhardjo, 2001;Nazir et al, 2014;Shanaev & Ghimire, 2019) on the stock markets. The negative impact of the recent coronavirus disease (COVID-19) outbreak on the world economy and capital markets is inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…The extant literature provides several empirical pieces of evidence on stock market responses to the major systemic events. The studies investigate the impact of major events, for instance, the Severe Acute Respiratory Syndrome (SARS) pandemic disease outbreak (Chen et al, 2007(Chen et al, , 2018Loh, 2006), natural disasters (Caporale et al, 2019;Tavor & Teitler-Regev, 2019;Wang & Kutan, 2013), corporate events (Maitra & Dey, 2012;Ranju & Mallikarjunappa, 2019;Seal & Matharu, 2018), public news (Li, 2018;Ormos & Vázsonyi, 2011) and political events (Beaulieu et al, 2006;Bash & Alsaifi, 2019;Ismail & Suhardjo, 2001;Nazir et al, 2014;Shanaev & Ghimire, 2019) on the stock markets. The negative impact of the recent coronavirus disease (COVID-19) outbreak on the world economy and capital markets is inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that stock market returns are responsive to major global events. These empirical papers examine how major global phenomena, such as the Severe Acute Respiratory Syndrome (SARS) pandemic outbreak (Chen et al 2018 , 2009 ; Loh 2006 ; Feng and Li 2022 ), Ebola (Ichev and Marinč 2018 ), HIV/Aids (Kauffman and Weerapana 2006 ; Daly et al 2019 ), natural and anthropogenic disasters (Kowalewski and Śpiewanowski 2020 ; Caporale et al 2019 ; Tavor and Teitler-Regev 2019 ; Wang and Kutan 2013 ), political (Bash and Alsaifi 2019 ; Shanaev and Ghimire 2019 ; Sajid Nazir et al 2014 ) and sporting events (Buhagiar et al 2018 ) influences stock market returns. Nonetheless, examining the impact of the COVID-19 epidemic on an economy is vital and cannot be emphasised enough, particularly in Ghana, a key destination for many international investments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Guglielmo Maria Caporale, Alex Plastun and Inna Makarenko (2019), considering the particularities of force majeure events and their influence on the Ukrainian stock market, outline the unexpected nature of force majeure events and therefore the impossibility of incorporation of them into asset prices in advance. Even more, as scientists point out, together with natural disasters, social, military and political events, economic events (for example, unexpected bankruptcies of legal entities) in some cases could be considered as force majeure [ 8 , p. 335]. The authors must agree with Olga Melnik (2018) who highlights that in modern researches of force majeure mainly historical aspects of formation of this category, its features are analysed, however the conditions of release from liability in the contractual relations, the problems of recognition of certain situations as force majeure and consequences of such situations are not studied.…”
Section: References Reviewmentioning
confidence: 99%